2016
DOI: 10.1016/j.ajur.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fever and sepsis after percutaneous nephrolithotomy

Abstract: ObjectivePercutaneous nephrolithotomy (PCNL) is commonly used in the management of large renal stones. Postoperative infections are one of the most common complications of this procedure. The present study is to determine and assess the factors that may increase the risk to develop fever and urinary sepsis after PCNL.MethodsA total of 60 patients (38 males and 22 females) with a mean age of 40.25 years enrolled in this study in Sulaimania Teaching Hospital. Patients had renal stone disease need operation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
2
24
4
Order By: Relevance
“…PCNL surgery brings about a stress response and backflow of pathogens and toxins, which accelerates the spread of infection and further leads to the occurrence of sepsis. Unlike other studies that only focus on local factors 20,21 , our study found that AGR, a systemic factor, maybe one of the important predictive factors of sepsis after PCNL. Another systemic factor noted in our study to be closely related to sepsis after PCNL is preoperative leukocytosis (RR=3.706, P =0.006).…”
Section: Discussioncontrasting
confidence: 87%
“…PCNL surgery brings about a stress response and backflow of pathogens and toxins, which accelerates the spread of infection and further leads to the occurrence of sepsis. Unlike other studies that only focus on local factors 20,21 , our study found that AGR, a systemic factor, maybe one of the important predictive factors of sepsis after PCNL. Another systemic factor noted in our study to be closely related to sepsis after PCNL is preoperative leukocytosis (RR=3.706, P =0.006).…”
Section: Discussioncontrasting
confidence: 87%
“…Similar results were seen in other studies 1,8,[10][11] while in the study in the Department of Urology of Mayo Clinic, it was observed in only 9% of patients. 5 Sepsis was seen in 6.2 % of patients which was similar to other results 4,[11][12] while Mayo clinic study showed low sepsis rates which was as low as 0.9 % . 5…”
Section: Discussionsupporting
confidence: 83%
“…11 Another study from Iraq showed positive association of sepsis with number of stones, duration of operation time, total leukocyte count, hemoglobin level and residual stone. 4…”
Section: Discussionmentioning
confidence: 99%
“…Less aggressive strategies would avoid risky interventions and increase the possibility of repeated treatment. Multiple punctures, supracostal access and a longer surgical duration may be needed for complex stones, but these risk factors significantly increase the complication rates of bleeding, fever, and renal function impairment . Other studies reported initial and final SFRs of 35.7–52.1% and 71.7–88.3%, respectively, after PCNL in patients with a SK , which means a balance between higher SFRs and lower complication rates can be attained in large experienced centres.…”
Section: Discussionmentioning
confidence: 99%